(untitled) (European Journal of Interdisciplinary Studies, 2015)
The Establishment and the consolidation of the legal state in the Republic of Macedonia still remains the main challenge and a primary issue which comes into view continuously during the functioning and the governance of this country, although we are facing the third decade of democratic transition since the fall of communism in these regions. By a legal state in Macedonia we understand the system in which the state authorities in this country, and in particular the executive and administrative authorities, though restricted to its legal norms (the constitution and the law) which guarantee the inviolability of fundamental human rights and freedoms of its citizens and the democratic functioning of political power, their implementation in practice nevertheless continues to represents a major difficulty that the country faces.The need of a functional legal state in Macedonia is still far from its implementation and in consistency with the theory of Hans Kelsen about the legal state. According to him, in the territorial region of a state there should be a single lawful, legitimate and sovereign order: that of the state: all the legal norms, directly or indirectly, derive from the state and those are valid only when incorporated in its lawful order, by thoroughly respecting their intentions. “The state represents the overall legal order, its law, being the highest, is the single true law”. We shall stop and focus on some of the main criteria, principles and pillars on which it relies, respectively on those which condition and enable the functioning of a legal state in Macedonia. These are the criteria and principles which are also accepted by the judicial-constitutional concept in general. Firstly, we will examine the respect of the principle of constitutionality and legality, the respect of the basic human rights and freedoms in this country: the free and democratic elections, independent courts etc.